Spectrophotometric Determination of Benzocaine by Azo-Dye Formation Reaction with N - (1-naphthyl)ethylenediamine as Coupling Agent - W. Bashir; N. Othman (College of Education for Pure Sciences, 2005)
A simple spectrophotometric method for the determination of benzocaine in aqueous solution is developed. The method based on the coupling of diazotized benzocaine with N-(1-naphthyl)ethylenediamine(N-NED) in acidic rnedium. The purplish - violet azo dye formed is water soluble, stable, and shows tnaximum absorption at 547.5 nm. Beer's law is obeyed over the range 10 - 100 ptg I 25 ml, i.e, 0.4 - 4 ppm with a molar absorptivity of 5.56 x 104l.mol-r.cm-' and Sandell's sensitivity index of 0.0029 pg.cm-2, arelative error of - 0.660 to * 0.002% and a relative standard deviations of*0.110to+ 0.550% depending on the concentration. The method has been applied to determine benzocaine in two synthetic pharmaceutical preparations.